Is Accounting a Measurement Discipline? - Vickrey, Don W. (The Accounting Review, 1970)
Abstract The article identifies the conditions for classifying accounting as a measurement discipline. A typical definition of measurement is "the assignment of numerals to objects or events according to rules." Defining measurement in this manner overcomes the objections mentioned above and insures that measures obtained via the various scales will be informative and consistent. A more satisfactory definition of measurement is the assignment of numerals to represent elements or a property of elements in a specified system on the basis of isomorphism or homomorphism existing between one or more empirical relational systems and one or more numerical relational systems. For example, if purchasing power, which is defined as the ability of an object to command other objects and services in exchanges, is shown to satisfy the conditions above, more precise definitions of accounting concepts could be formulated. Similarly, in choosing a depreciation method for a particular asset, the accountants would choose the method which is believed to parallel more closely the decline in the purchasing power of the asset. If accountants are not willing to choose an economic property for accounting measurement, which approximates extensiveness, and to assume that the property is extensive, they must abandon their attempts to improve and to explain accounting via measurement theory.